Molecular dynamics simulations suggest that RNA three-way junctions can act as flexible RNA structural elements in the ribosome - Besseová, Ivana; Réblová, Kamila; Leontis, Neocles B; Sponer, Jirí (Nucleic acids research, 2010)
We present extensive explicit solvent molecular dynamics analysis of three RNA three-way junctions (3WJs) from the large ribosomal subunit: the 3WJ formed by Helices 90-92 (H90-H92) of 23S rRNA; the 3WJ formed by H42-H44 organizing the GTPase associated center (GAC) of 23S rRNA; and the 3WJ of 5S rRNA. H92 near the peptidyl transferase center binds the 3'-CCA end of amino-acylated tRNA. The GAC binds protein factors and stimulates GTP hydrolysis driving protein synthesis. The 5S rRNA binds the central protuberance and A-site finger (ASF) involved in bridges with the 30S subunit. The simulations reveal that all three 3WJs possess significant anisotropic hinge-like flexibility between their stacked stems and dynamics within the compact regions of their adjacent stems. The A-site 3WJ dynamics may facilitate accommodation of tRNA, while the 5S 3WJ flexibility appears to be essential for coordinated movements of ASF and 5S rRNA. The GAC 3WJ may support large-scale dynamics of the L7/L12-stalk region. The simulations reveal that H42-H44 rRNA segments are not fully relaxed and in the X-ray structures they are bent towards the large subunit. The bending may be related to L10 binding and is distributed between the 3WJ and the H42-H97 contact.
Keywords: simulace molekulární dynamiky; RNA, Ribosomal, 5S; Phosphates; RNA, Ribosomal, 23S; RNA, Bacterial; konformace nukleové kyseliny; bakteriální RNA; Escherichia coli; Nucleic Acid Conformation; fosfáty; RNA ribozomální 5S; RNA, Archaeal; Molecular Dynamics Simulation; Haloarcula marismortui; RNA ribozomální 23S; archeální RNA